2023
DOI: 10.1186/s43093-023-00213-4
|View full text |Cite
|
Sign up to set email alerts
|

Does ownership structure reduce earnings manipulation practice of Egyptian listed firms? Evidence from a dynamic panel threshold model

Abstract: This paper analyzes the nonlinear relationship between corporate ownership structure and income manipulation through accrual-based earnings management in the Egyptian context. To do so, we develop a sample of 78 listed non-financial firms, covering the period 2008–2017. Using the dynamic panel threshold analysis approach (Seo and Shin in J Econom 195: 169–186, 2016), we found a nonlinear relationship between ownership structure and earnings manipulations. This proves the presence of an optimal ownership struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…In summary, risk disclosure is an important contributor to the improvement in a firm's overall performance. It builds stakeholder trust, reduces conflicts of interest, and limits earnings management practices [24,43]. This highlights the strategic importance of disclosing risk in the financial and managerial context of modern firms [19,44].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…In summary, risk disclosure is an important contributor to the improvement in a firm's overall performance. It builds stakeholder trust, reduces conflicts of interest, and limits earnings management practices [24,43]. This highlights the strategic importance of disclosing risk in the financial and managerial context of modern firms [19,44].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…More recently, Ref. [24] concluded that the association between ownership and earnings manipulation is nonlinear. Their outcomes reveal that the ownership structure of Egyptian firms has alignment effects on earnings management.…”
Section: Empirical Review and Hypotheses' Developmentsmentioning
confidence: 99%
See 1 more Smart Citation